1978
DOI: 10.1159/000468329
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam and Halazepam in Anxiety: some Prognostic Indicators

Abstract: A multiple step-search regression procedure was applied to data obtained with 37 diazepam and 42 halazepam treated anxious outpatients. Good treatment outcome was predicted for those patients who reported a more adequate family adjustment, the presence of precipitating stress, and who either had no prior psychotropic drug treatment, or if they had received such treatment, had experienced a good response. Probably of greatest interest to the practicing clinician was the observation that patients high in initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…An early study of benzodiazepines suggested that low interpersonal problems predicted a good anxiolytic response in "anxious" outpatients, though diagnoses were not clearly specified in this paper [76].…”
Section: Anxiety Disordersmentioning
confidence: 73%
“…An early study of benzodiazepines suggested that low interpersonal problems predicted a good anxiolytic response in "anxious" outpatients, though diagnoses were not clearly specified in this paper [76].…”
Section: Anxiety Disordersmentioning
confidence: 73%